Research on Wavelength-Shifting Fiber Scintillator for Detecting Low-Intensity X-Ray Backscattered Photons - Baolu Yang; Zhe Yang; Xin Wang; Baozhong Mu; Jie Xu; Cheng Yang; Hong Li (Photonics)
High-sensitivity fiber scintillator detectors are the key to achieving high signal-to-noise ratio and high contrast imaging in X-ray Compton backscattering technology. We established a simulation model of wavelength-shifting fiber (WSF) scintillator detectors based on Geant4. The influences of ray source energy, detection area, number of WSFs, and coupling mechanism on detection efficiency were simulated. By using the epoxy resin coupling method, the transmission efficiency between the WSF and scintillator was increased from 4.56% to 19.79%. Based on the simulation data, we developed an X-ray WSFs scintillator detector, built an X-ray backscattering imaging experimental system, obtained high-contrast backscattering images, and verified the performance of the detector.